Plight of Chemistry Teachers in Remote Teaching during COVID-19 Pandemic - Kumar, Narendra; Nidhi; Srinivasan, Easwar (Voices of Teachers and Teacher Educators, 2022)
Sudden emergence of COVID-19 pandemic disrupted the whole system across the globe, severely affecting the social, economic and education system affecting the pattern of teaching from traditional face-to-face (F2F) teaching-learning to remote learning. Remote teaching is defined as the technology-enhanced teaching methodology where both the students and teachers are separated at both geographical and time differences and the process of teaching and learning takes place outside the four walls of the classroom and in a setting most suitable to their situation. This work focuses on the challenges encountered by Senior Secondary teachers of Chemistry subject from Private or Government Schools and Inter Colleges in Patna District, Bihar, India and some pre-service teachers’ questionnaire based survey with 55 respondents. The survey indicates that the major problem in remote teaching is the assessment of students, providing feedback to the students and other issues pertaining to adaptability, arranging for resources along with technical errors and internet connectivity. A solution to all the problems can be achieved when teachers are more acquainted with internet-based technologies and online teaching tools, adjust their teaching plans and teaching methods, and quickly adapt to the new situation. Enhanced interactions among each other, maintenance of interest, consistent motivation and support to be dispended to learners as well as teachers for improvement in the teaching-learning process.